Fantasia e creatività in Bruno Munari - Cantelli, Chiara (Studi sulla Formazione/Open Journal of Education, 2019)
The essay aims to outline the poetics underlying the whole activity of Bruno Munari, a unique and polyhedric character having been an artist, a designer and, last but not least, a creator of educational workshops for children aimed at developing a creative learning process; activities that, despite their discreet appearance, are interwoven. According to the three classic distinctions between "Munari-Artist", "Munari-Designer" and "Munari-Pedagogist", none of these three poles is comprehensible without presupposing the other two: among them is persisting an intrinsic as mandatory and dynamic correlation that, if broken or overlooked, undermines any chance to understand the unity of the "Munari-Universe". This unity resides in the conception that Munari has of art: conceived as an activity at the service of life to be born out of life itself as a reality in continuous transformation, art finds its focal point in creativity that on turn, understood as integration of rule and chance, logic and fantasy, technique and play, functionality and unrestricted availability, necessity and freedom, is also recognized as the distinctive character of human intelligence.